2013
DOI: 10.1073/pnas.1306623110
|View full text |Cite
|
Sign up to set email alerts
|

Energetic basis of catalytic activity of layered nanophase calcium manganese oxides for water oxidation

Abstract: Previous measurements show that calcium manganese oxide nanoparticles are better water oxidation catalysts than binary manganese oxides (Mn 3 O 4 , Mn 2 O 3 , and MnO 2 ). The probable reasons for such enhancement involve a combination of factors: The calcium manganese oxide materials have a layered structure with considerable thermodynamic stability and a high surface area, their low surface energy suggests relatively loose binding of H 2 O on the internal and external surfaces, and they possess mixed-valent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
76
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 41 publications
1
76
0
Order By: Relevance
“…We then focused on the energetics of nanosheets of calcium manganese oxide (CaMnO). We found that these layered phases are highly thermodynamically stable and have significantly lower surface energy than the binary manganese oxides Mn 3 O 4 , Mn 2 O 3 , and MnO 2 (7). The enthalpy of oxidation of CaMnO materials was independent of the average oxidation state and significantly less exothermic that the oxidation of Mn 2 O 3 to MnO 2 .…”
Section: Discussion: Geochemical and Technological Implicationsmentioning
confidence: 86%
See 1 more Smart Citation
“…We then focused on the energetics of nanosheets of calcium manganese oxide (CaMnO). We found that these layered phases are highly thermodynamically stable and have significantly lower surface energy than the binary manganese oxides Mn 3 O 4 , Mn 2 O 3 , and MnO 2 (7). The enthalpy of oxidation of CaMnO materials was independent of the average oxidation state and significantly less exothermic that the oxidation of Mn 2 O 3 to MnO 2 .…”
Section: Discussion: Geochemical and Technological Implicationsmentioning
confidence: 86%
“…The method titrates iodine produced by the reaction of iodide with dissolved manganese and can be performed at room temperature. The specific details of the titration of Mn(III and IV) oxidation state and calculations are described in detail elsewhere (7). The enthalpy of water adsorption was measured by calorimetry at room temperature using a Calvet microcalorimeter, coupled with a Micromeritics ASAP 2020 analysis system as described previously (4).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, one of the biggest challenges is to develop a cheap and efficient catalyst for the former reaction with a low overpotential, which is still needed to overcome the kinetic barriers (already lowered by the catalyst) along the path from reactants to products. Birnessite, similar to the oxygen-evolving complex in Photosystem II for photosynthesis in regard to the coexistence of Mn(III) (nominal Mn 3+ ) and Mn(IV) (nominal Mn 4+ ) within its structure (1)(2)(3), has already shown a moderate catalytic performance with the overpotentials reported from 0.6 V to 0.8 V (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Mn-based cluster compounds (15, 16) and disordered birnessite nanoparticles (2) can exhibit analogous reactivity to the water-oxidizing center of photosystem II. Metal reduction is a key step in water oxidation using Mn oxide catalysts (2,15,17,18) with evidence that Mn(III) plays an important role in O 2 generation (19). However, no information on the intrinsic kinetics or efficiency of Mn(IV) reduction has been reported to date.…”
mentioning
confidence: 99%
“…However, no information on the intrinsic kinetics or efficiency of Mn(IV) reduction has been reported to date. The structural and chemical constraints on the mechanism of Mn photoreduction are not known for any Mn phase (17,18), although a recent study of MnO 2 -based water oxidation showed that the substitution of Na with Ca in the interlayer of MnO 2 greatly enhances reactivity (15). The mineralogy literature suggests that the interlayer cations, which balance the excess charge in the MnO 2 sheet, may influence its photoreactivity because the interlayer cations are known to bind water molecules to the neighboring MnO 2 octahedral sheets via hydrogen bonding, with the strength of the interactions dependent on the cation valence (20)(21)(22).…”
mentioning
confidence: 99%